2010
DOI: 10.1111/j.1432-2277.2010.01183.x
|View full text |Cite
|
Sign up to set email alerts
|

Living donor liver transplantation: effect of the type of liver graft donation on donor mortality and morbidity

Abstract: Summary To investigate the influence of the type of liver graft donation on donor mortality and morbidity. The clinical course of 87 living liver donors operated on at our center between 2002 and 2009 was retrospectively analysed and data pertaining to all complications were retrieved. No donor mortality was observed and no donor suffered any life‐threatening complication. Four donors (4.6%) developed biliary leakage, nine (10.3%) had to be readmitted to hospital and six (6.9%) required some or other type of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 32 publications
1
52
1
1
Order By: Relevance
“…Our study revealed a 25.3% donor morbidity rate using the Clavien 5-tier grading system after a median follow-up of 62 mo, which was similar to Kousoulas’ report [13] but much lower than Azoulay’s report of an overall complication rate of 47.3% [7]. The much higher complication rate in the Azoulay study was caused by the inclusion of only right lobe donations; intra-operative complications were also included.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Our study revealed a 25.3% donor morbidity rate using the Clavien 5-tier grading system after a median follow-up of 62 mo, which was similar to Kousoulas’ report [13] but much lower than Azoulay’s report of an overall complication rate of 47.3% [7]. The much higher complication rate in the Azoulay study was caused by the inclusion of only right lobe donations; intra-operative complications were also included.…”
Section: Discussionsupporting
confidence: 84%
“…In general, the potential risks associated with adult-to-adult LDLT are greater than with adult-to-child LDLT due to the extensive surgery and the smaller donor remnant in the former [26]. However, Kousoulas [13] indicated that there was no significant difference in the complication rates among the right lobe, left lobe and left lateral lobe donors after operation, that the severity of complications was comparable and that donor mortality and morbidity did not differ; however, right lobe donation was associated with prolonged hospital stay, increased frequency of blood transfusions and prolonged operation time compared with left and left lateral lobe donation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has important implication in living donation favoring left donation as far as this would have negative impact on the recipient. 12,28,34,[40][41][42][43] In liver surgery, an important endpoint-often imbedded in the reporting of complications-is postoperative liver failure, also labeled ''small-for-size'' syndrome, 10,44,45 although no consensus exists on this definition. We tested 4 commonly used definitions, [7][8][9][10] and found that only 1, ISGLS, 7 captured some postoperative liver dysfunction in this series.…”
Section: Discussionmentioning
confidence: 99%
“…3,10,11 Overall, approximately 10% of left lobe donors 3 and one-third of all right lobe donors 4 experience LDLTrelated morbidity (ranging from minimal complications to serious ones). Deaths resulting from either technical failures or early postoperative problems underscore the reality that living donor hepatectomy is associated with the small but real possibility of donor death; the risk may approach 0.5% for right lobe donors and approximately 0.1% for left lobe donors.…”
Section: Analysis Question 1 Why Is Living Donation Necessary and Imentioning
confidence: 99%